How Digital Literacy Affects Indonesian Students' Motivation and Interest in Entrepreneurship - Suprianto*, Suprianto; Komara, Endang; P. Agung, Ign. Wiseto; Fauzzia, Willma (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study aims to investigate the impact of digital literacy on motivation and interest in entrepreneurship at the Mardira Indonesia College of Information and Computer Management (STMIK). A survey of 100 students was conducted using a quantitative approach. The results showed a significant positive effect of digital literacy on students' entrepreneurial motivation and interest. The implications of this research provide a deeper understanding of the importance of digital literacy in influencing student entrepreneurial attitudes and behaviors in the digital era. The implications of this research include increasing digital literacy awareness, the role of education in developing entrepreneurial skills, developing entrepreneurship coaching programs, and increasing career opportunities and economic independence of students. Keywords: Digital literacy; Digitalization; Entrepreneurial Motivation; Entrepreneurial Interest; Student’s Motivation